Establishment of a Predictive In Vitro Assay for Assessment of the Hepatotoxic Potential of Oligonucleotide Drugs - Sewing, Sabine; Boess, Franziska; Moisan, Annie; Bertinetti-Lapatki, Cristina; Minz, Tanja; Hedtjaern, Maj; Tessier, Yann; Schuler, Franz; Singer, Thomas; Roth, Adrian B. (PLOS ONE, 2016)
Single stranded oligonucleotides (SSO) represent a novel therapeutic modality that opens new space to address previously undruggable targets. In spite of their proven efficacy, the development of promising SSO drug candidates has been limited by reported cases of SSO-associated hepatotoxicity. The mechanisms of SSO induced liver toxicity are poorly understood, and up to now no preclinical in vitro model has been established that allows prediction of the hepatotoxicity risk of a given SSO. Therefore, preclinical assessment of hepatic liability currently relies on rodent studies that require large cohorts of animals and lengthy protocols. Here, we describe the establishment and validation of an in vitro assay using primary hepatocytes that recapitulates the hepatotoxic profile of SSOs previously observed in rodents. In vitro cytotoxicity upon unassisted delivery was measured as an increase in extracellular lactate dehydrogenase (LDH) levels and concomitant reduction in intracellular glutathione and ATP levels after 3 days of treatment. Furthermore, toxic, but not safe, SSOs led to an increase in miR-122 in cell culture supernatants after 2 days of exposure, revealing the potential use of miR122 as a selective translational biomarker for detection of SSO-induced hepatotoxicity. Overall, we have developed and validated for the first time a robust in vitro screening assay for SSO liver safety profiling which allows rapid prioritization of candidate molecules early on in development.